Both pre- and post-synaptic alterations contribute to aberrant cholinergic transmission in superior cervical ganglia of APP−/− mice. (November 2016) - Cai, Zhao-Lin; Zhang, Jia-Jia; Chen, Ming; Wang, Jin-Zhao; Xiao, Peng; Yang, Li; Long, Cheng
Abstract: Though amyloid precursor protein (APP) can potentially be cleaved to generate the pathological amyloid β peptide (Aβ), APP itself plays an important role in regulating neuronal activity. APP deficiency causes functional impairment in cholinergic synaptic transmission and cognitive performance. However, the mechanisms underlying altered cholinergic synaptic transmission in APP knock-out mice (APP −/− ) are poorly understood. In this study, we conducted in vivo extracellular recording to investigate cholinergic compound action potentials (CAPs) of the superior cervical ganglion (SCG) in APP −/− and littermate wild-type (WT) mice. Our results demonstrate that APP not only regulates presynaptic activity, but also affects postsynaptic function at cholinergic synapses in SCG. APP deficiency reduces the number of vesicles in presynaptic terminalsand attenuatesthe amplitude of CAPs, likely due to dysfunction of high-affinity choline transporters. Pharmacological and biochemical examination showed that postsynaptic responsesmediated by α4β2 and α7 nicotinic acetylcholine receptors are reduced in the absence of APP. Our research provides evidences on how APP regulates cholinergic function and therefore may help to identify potential therapeutic targets to treat cholinergic dysfunction associated with Alzheimer's disease pathogenesis. Highlights: APP is required to maintain cholinergic synaptic transmission in SCG. APP preserves repetitive cholinergic neurotransmission by presynaptic CHT. APP contributes to postsynaptic function by assisting α4β2 and α7 nAChRs. APP protects synaptic structure in presynaptic vesicle pool and PSD length.